Letter to Jane Tolmach; from James T. Shelton - James T. Shelton:::::: (1968)
This letter to Jane Tolmach from James T. Shelton (Superintendent & Medical Director) sent on March 7, 1968 is a response to Mrs. Jane's letter to Mrs.Krier in regards Camarillo State Hospital Advisory Board visiting Porterville State Hospital on Thursday, March 28, 1968. Mrs.Krier as stated in the letter are planning a luncheon for the Board of Trustees, Porterville State Hospital Policy Group, and Camarillo's Administrative Assistant. But in order to make it to Porterville they must fly not later than 10:30 am due to it being a 45 minute trip in airplane.